Energias renováveis no Brasil - PEREIRA, Silvio Martins Rodrigues (173, 2022)
Hoje em dia com o avanço das novas tecnologias surgiram várias formas de energias renováveis. Como exemplo, temos a energia vinda das placas solares, o biogás, a biomassa, eólica, energia hidrelétrica, geotérmica, oceânica, etc. Porém, ainda se produz energia de fontes não renováveis como o petróleo que polui o planeta com resíduos sólidos e atmosféricos, e que poderiam ser reciclados ou utilizados como fonte de energia. Um exemplo de produção de energia limpa são as usinas de açúcar e etanol que aproveitam praticamente toda sua matériaprima de forma renovável e sustentável. Dessa forma, as energias renováveis diminuem a poluição em lençóis freáticos, nascentes e no ar, como também, ajudam a minimizar os problemas de saúde, o efeito estufa global e o uso desenfreado de recursos naturais, oferecendo para todas as sociedades, uma qualidade de vida melhor para gerações atual e futura.

Today, with the advancement of new technologies, there are several forms of renewable energy around the world. As an example, we have energy from solar panels, biogas, biomass from sugarcane bagasse that generates steam, hydraulic energy, pneumatic energy, wind, hydro, geothermal, oceanic energy, etc. Because today we have many sources of pollution from nonrenewable energies such as oil, things that generate garbage and residues, which could be recycled or used as a source of energy, as we have today the plant that was only producing sugar and today uses practically all its material raw, which is the cane that is used in a renewable and sustainable way. Types of energies that end up saving groundwater and springs, good renewable energy also prevents greater air pollution that would harm birds and even aircraft, in addition to the greenhouse effect that increases the earth's temperature and destroys the ozone layer, contributes to our health. for having cleaner air of better quality and a better way of life. Thinking about the next generations our children.
Renewable energies in Brazil
Keywords: Fontes renováveis de energia; Meio ambiente; Desenvolvimento sustentável; Ambiente e Saúde